Identifikasi Senyawa Fitokimia dan Uji Aktivitas Antioksidan Ekstrak Etanol Limbah Kulit Biji Kakao (Theobroma cacao L.) Varietas Trinitario - Haryadi, Celvin; Wirawan, I Gede Putu; Sritamin, Made (Agrotrop : Journal on Agriculture Science, 2023)
Identification of Phytochemical Compounds and Antioxidant Activity Test of Ethanol Extract of Cocoa Bean Shell Waste ( Theobroma cacao L.) Trinitario Varieties . Cocoa is one of the mainstay commodities of plantations in Indonesia, contributing to the country's foreign exchange earnings. Byproducts such as fruit skins and pulp are produced during the production of dry cocoa beans, and waste in the form of cocoa bean husks is produced during the processing of dry cocoa beans into chocolate products. So far, cocoa bean husk waste has not been used optimally, leading to a low economic value. The purpose of this study was to determine the bioactive compounds in the skin and the levels of antioxidant compounds in cocoa bean husk waste so that it could be used as a raw material for medicine. The GC-MS analysis method was used to identify bioactive compounds in cocoa bean husk waste, and the DPPH method was used to test antioxidant activity. According to the results of the GC-MS analysis, the cocoa bean husk waste extract contains four compounds with quality value higher than 90. These four compounds are Alpha-Copaene, Copaene, Caryophyllene, and Caffeine. The antioxidant test results of the cocoa bean husk waste extract revealed an IC 50 value of 86,213 ppm, indicating strong antioxidant activity because the IC 50 value is between 50-100 ppm.